Toward multidisciplinary and integrative MHPSS services in the Kurdistan Region: highlighting the role of clinical social work as a bridging field (Discussion Paper) - amin, Dyari S. Hama amin Hama (Sulaimani Journal for Humanities, 2026)
The mental health psychosocial support field is moving toward integrative work; clinicians and scholars reiterate the importance of an interactive approach as it allows services to be adapted to the unique needs and backgrounds of the clients. Additionally, now, more than ever, multidisciplinary work is highly recommended to achieve significant results and provide much-needed comprehensive services. These services range from community-based psychosocial support activities to highly specialized interventions. Although progress has been made toward having experts from fields such as clinical psychology and psychotherapy in the Kurdistan region, gaps still remain, especially in terms of closing the gaps that exist in providing services. The emergence of social work is an essential step towards having effective and trained social workers who function as case managers and case workers. However, this paper argues that the field of clinical social work is required in the Kurdistan Region since it allows us to connect the specialized psychotherapy provision to social work functions. Clinical social workers possess significant similarities and differences with clinical psychology. Clinical social workers take a more holistic approach to their intervention. They also consider how society and the environment influence the client's well-being; this is highly relevant to the Kurdistan Region as its population has a traumatic history, and the region has prolonged conflict. This paper highlights the necessity of clinical social work and its role in moving toward a more integrative and multidisciplinary approach to MHPSS services.
Keywords: Clinical social work; MHPSS; Kurdistan Region; Integrative approach; Multidisciplinary